2014
DOI: 10.3171/2014.3.jns131140
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of resection and intraoperative cesium-131 radioisotope brachytherapy in patients with newly diagnosed brain metastases

Abstract: Object Resected brain metastases have a high rate of local recurrence without adjuvant therapy. Adjuvant whole brain radiotherapy (WBRT) remains the standard of care with the rate of local control >90%. However, WBRT is delivered over 10–15 days, which can delay other therapy and is associated with acute and long-term toxicities. Intra-operative permanent Cesium-131 (Cs-131) implants can be performed at the time of surgery, thereby avoiding any additional therapy. We evaluate the safety, feasibility and effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 67 publications
1
66
0
Order By: Relevance
“…Clinical studies have shown that TISSEEL fibrin glue is biocompatible and biostable in the brain of human patients 18 . Importantly, these properties have led to the use of fibrin scaffolds for tissue engineering of adipose, skin, liver, and bone tissues 19 , delivery of therapeutic molecule for various diseases 19,20 , and brachytherapy treatment of brain tumors 2123 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that TISSEEL fibrin glue is biocompatible and biostable in the brain of human patients 18 . Importantly, these properties have led to the use of fibrin scaffolds for tissue engineering of adipose, skin, liver, and bone tissues 19 , delivery of therapeutic molecule for various diseases 19,20 , and brachytherapy treatment of brain tumors 2123 .…”
Section: Introductionmentioning
confidence: 99%
“…43 Local therapy with intraoperative radiation or brachytherapy may be a particularly attractive option for lesions that result in resection cavities too large to be treated safely with SRS such as those great than 15 ml in volume. 44,45 Local radiation to the resection cavity, either via SRS or intraoperative radiotherapy, has been associated with an increased rate of distant failure and leptomeningeal disease in comparison to adjuvant WBRT. 46 Leptomeningeal disease is associated with breast histology and infratentorial location.…”
Section: Radiosurgery To the Resection Cavitymentioning
confidence: 99%
“…Treatment technique has been previously described [23]. In short, patients underwent maximally safe neurosurgical resection of lesions.…”
Section: Treatment Techniquementioning
confidence: 99%
“…However, the main criticism of these studies, the majority of which involved I-125 implants, was the high rate of radiation necrosis from 5 % up to 23 % in one series [19][20][21][22]. Intraoperative permanent Cesium-131 (Cs-131) implants may provide a viable alternative to WBRT with high response rates and minimal toxicity [23]. We have previously reported very promising results from our prospective series of 24 patients who received surgical resection with intraoperative Cs-131 brachytherapy achieving excellent local control and minimum toxicity.…”
Section: Introductionmentioning
confidence: 96%